Avaliação clínica e laboratorial dos efeitos biológicos das sementes de chia (salvia hispanica l.) Em portadores de doenças crônicas e indivíduos saudáveis. - Alessandra de Cássia Lovato (2021)
Chia (Salvia hispanica L.) is an herbaceous plant, with high oil content, mainly Omega 3, proteins, dietary fibers and other bioactive compounds. It has been studied for its important nutritional composition, potential functional action and for its beneficial health effects. The aim of this study was to evaluate the effects of eating chia seeds on human biological markers, such as clinical and anthropometric, glycemic, lipid and inflammatory profiles. Blood glucose levels, glycated hemoglobin, total cholesterol, their fractions and triglycerides were evaluated by colorimetric tests; for the determination of resistin levels, the enzyme immunoassay (ELISA) was used; the antioxidant capacity of plasma was evaluated by the MTT (tetrazolium salt) reduction assay. For the patient group, 34 individuals with chronic diseases [Type 2 Diabetes mellitus (DM2), Systemic arterial hypertension (SAH) and obesity] and 24 healthy individuals belonging to the control group were selected. The collaborators of the research consumed 20 grams of chia seeds daily for six months, the biomarkers being measured at the beginning of the study [Time 0 (T0) - before Chia consumption] and at the end [Time 6 (T6) - six months after consuming Chia]. The results obtained in the research showed an improvement in the lipid profile, in the antioxidant potential of the plasma, as well as in its anthropometric measurements of weight, circumferences (abdominal and waist) and body mass index, with statistical significance. For the other evaluated markers, no differences were found. It is concluded that chia seeds can act as a potential functional food to improve anthropometric and laboratory clinical parameters in patients with chronic diseases. In this way, chia could act as an adjunct in the prevention and control of chronic metabolic disorders, which would encourage more clinical research in this context.